Aspectos da qualidade de vida no trabalho dentro do gerenciamento estratégico na construção civil : estudo de caso em um empreendimento residencial multifamiliar - Gonçalves, Caroline de Lima Zanon (2017)
The work is often the place where we spend most time of our lives. Having a favorable environment and work conditions are factors that influence the quality of work life of each person. Such conditions in civil construction are generally not the best, exposing workers to precarious and often risky situations. The objective of this research was to investigate how aspects of quality of work life, within the strategic management, influence work environment conditions and performance indicators of the workforce in a civil construction development.Thus, as the research strategy, it was adopted the case study of a multifamily residential development, with data collection through the application of interviews and information provided by the company. It was possible to verify that the costs for the implementation of environments and working conditions were 1.33%, while an average of 1% of this investment is in average estimated. It was observed indicators of permanence time higher than civil construction averages and, accident frequency and severity rates of 9% and 15%, respectively, values considered very good on the scale established by the International Labor Organization. It was possible to conclude that the strategic management adopted presents economic viability in relation to the reality of better environments and working conditions, besides satisfactory results in the performance indicators of the labor that were analyzed.